PENGARUH ROA, LEVERAGE, KOMITE AUDIT, SIZE, SALES GROWTH TERHADAP TAX AVOIDANCE - YOHAN YOHAN; ARYA PRADIPTA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this research to examine the factors that influencing Tax Avoidance. Those factors are Return on Asset (ROA), Leverage, Audit Committee, Size, and Sales Growth to Tax Avoidance. The population of this research is manufactured companies which consistently listed in Indonesia Stock Exchange from 2013 to 2015. Samples are obtained through purposive sampling method, in which only 69 of listed manufactured companies in Indonesia Stock Exchange meet the sampling criterias resulting 207 data available are taken as the samples. This research used multiple regression method to test the effect of each variable in influencing tax avoidance. The result of this research indicates that Return on Asset has influence toward Tax Avoidance, while Leverage, Audit Committee, Size and Sales Growth have no influence toward Tax Avoidance.